COMMUNICATION STRATEGY IN HANDLING INDIHOME CUSTOMER COMPLAINTS AT THE TELKOM STO SUKARAMAI OFFICE - Astika Nisa Alfifa; Nursapia Harahap (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the communication strategies of service officers in handling IndiHome customer complaints at the Telkom STO Sukaramai Office and its impact on customer satisfaction. The study used a descriptive qualitative approach with data collection techniques through interviews and observations. Data analysis was carried out through reduction, presentation, and drawing conclusions, with triangulation techniques for validity. The results showed that communication was carried out interpersonally through direct interaction and digital media such as telephone and WhatsApp. Although officers have demonstrated a professional attitude and provided education to customers, communication effectiveness is still not optimal, especially in terms of message clarity and empathetic approach. In addition, service quality has not been consistent in terms of responsiveness and reliability. This condition causes the level of customer satisfaction to be in the fairly satisfied category. Therefore, it is necessary to improve the integration between communication strategies and service quality to improve customer satisfaction.